Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Sepeda Motor Honda Beat (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Bandar Lampung) - Toton Toton; Senna Enzovani; Bunga Vidya Putri (Universitas Mitra Indonesia, 2021)
ABSTRACTProblems in this research was motorcycle sales brand honda beat to PT .Astra Honda Motor experienced fluctuations , sales the highest was in april of 7,03 % , while declining sales the highest was in june of 5,63 %. The problems formulated is whether brand image and prices influential of the decision the purchase motorcycle honda beat in students of the Faculty Business And Economy University Bandar Lampung .Population in this research is students of the faculty business and economy university bandar lampung were 96 respondents , data collection use spss 23.0 version .Based on the results of discussion a conclusion can be drawn that obtained the regression equation is linear multiple of y = 8,018 + 1,084 x1 + 0,459 x2 , value f statistic of 58,608 with significance of 0.000 .Value the coefficients determination 75,4%.Keywords : Brand Image, Price, and Purchase Decision